IMPLEMENTING HYPERCORRECTION APPROACH TO REDUCE THE STUDENTS FOSSILIZATION IN ENGLISH PRONUNCIATION AT SMA NEGERI 7 SELAYAR - Hajar, Sitti; Prabawati Rum, Eka; Sastrawati, Ika (English Language Teaching Methodology, 2023)
The purpose based on this research was to find out whether or not the hypercorrection approach reduces the student’s fossilization in English pronunciation at SMA Negeri 7 Selayar. The researcher used a pre-experimental design and quantitative method using one class for a pre-test and post-test.In the 2022–2023 academic year, the population of this study were 32 students of class 10 IPA at SMA Negeri 7 Selayar. To determine the research sample, cluster sampling method is used. The speaking test is used a data collection method.The results show of the study show that the application of the hypercorrection approach can reduce the fossilization of students’ pronunciation in vowels (/i:/, /I/, /e/, /æ/). This is evidenced by using pre-test scores (39.53) and a post-tests score(72.18), which shows that in addition to the test scores, students’ pronunciation in the post-test is higher than the pre-test. (29.10) which is higher based on the t-table value (1.696). As a result, the Null hypothesis was refuted and the alternative hypothesis was adopted. In the study the researcher came to the conclusion that Hypercorrection reduces student’s fossilization of pronunciation.